Biotic Resistance to an Alien Amphibian: Larval Competition between Japanese Frogs and Invasive Cane Toads - Haramura, Takashi (PLoS One, 2016)
Understanding negative effects of native species on introduced taxa may suggest novel ways to control the invasive species by enhancing such effects. Previous studies have reported that the larvae of invasive cane toads (Rhinella marina) are suppressed by competition with the larvae of native anurans in Australia, but not in North America. We conducted laboratory trials to measure the effect of exposure to the larvae of Japanese frogs (Microhyla ornata, Fejervarya sakishimensis, Rhacophorus owstoni) on rates of survival, growth and development of cane toad tadpoles in Ishigaki Island, in southern Japan. Survival rates were not affected by native species, but competition with Dicroglossids and Rhacophorids (but not Microhylids) strongly reduced rates of growth and development in the tadpoles of cane toads. Dicroglossid tadpoles also reduced the body condition to toad tadpoles in addition to effects on SVL and mass. Encouraging populations of native frogs in toad-invaded areas of Japan thus may help to reduce the numbers of invasive cane toads.